Pattern recognition, machine intelligence and biometrics - Wang, Patrick S-P. (Patrick Shen-pei).; SpringerLink (Online service). (Beijing Higher Education Press Dordrecht New York Springer, 2011)
"Pattern Recognition, Machine Intelligence and Biometrics" covers the most recent developments in Pattern Recognition and its applications, using artificial intelligence technologies within an increasingly critical field. It covers topics such as: image analysis and fingerprint recognition; facial expressions and emotions; handwriting and signatures; iris recognition; hand-palm gestures; and multimodal based research. The applications span many fields, from engineering, scientific studies and experiments, to biomedical and diagnostic applications, to personal identification and homeland security. In addition, computer modeling and simulations of human behaviors are addressed in this collection of 31 chapters by top-ranked professionals from all over the world in the field of PR/AI/Biometrics. The book is intended for researchers and graduate students in Computer and Information Science, and in Communication and Control Engineering. Dr. Patrick S. P. Wang is a Professor Emeritus at the College of Computer and Information Science, Northeastern University, USA, Zijiang Chair of ECNU, Shanghai, and NSC Visiting Chair Professor of NTUST, Taipei.
Introductions and Editorial -- Fingerprint Analysis and Recognition -- Handwriting Analysis and Extraction -- Symbolic Factorial Discriminant Analysis for Face Recognition -- Noniterative 3D Face Reconstruction Based on Photometric Stereo -- Multimodal Biometrics by Face and Hand Images -- Signature Verification Technique Using Data Glove -- Performance Comparisons of Facial Expression Recognition in JAFFE Database -- Inverse Biometrics for Mouse Dynamics -- User Friendly Identification with Stepping -- Colored Faces and Facial Features Extractions -- Comparison of ROC and Likelihood Decision Methods in Fingerprint Analysis and Recognition -- Facial Metamorphosis for Biometric Applications -- Genetic Algorithm Using Fingerprint and Iris Biometrics -- Fingerprint Asymmetry Measures -- Application Iris Recognition Using Classifier Combination -- Development of Handwriting Recognition of Whiteboard Notes -- Recent Development of Speech Analysis and Recognition in Biometrics -- Case Studies of Ambiguities of Biometrics -- Conclusions, Open Problems, and Future Research -- Other Related Subtopics by Prominent Professionals.
Electronic reproduction.
Keywords: Optical pattern recognition; Artificial intelligence; Biometric identification; Computer vision; Human face recognition (Computer science).; Electronic books